Smart Irrigation System using IoT - S., Gunasekaran; A., Harini; S., Maithili; N., Dinahar S; R., Gowtham (Journal of ISMAC, 2025)
This study proposes an innovative smart irrigation system designed to address the inefficiencies of traditional methods. Utilizing sensors, microcontrollers, and other integrated components, the system ensures efficient water usage, promoting a more sustainable approach to agriculture. By providing real-time soil moisture monitoring and rainfall data, the system empowers farmers to make informed irrigation decisions, thereby improving crop management. Key features, such as a soil moisture sensor and rain sensor to prevent over-watering, enhance the system’s effectiveness in promoting optimal plant growth. Overall, this proposed smart irrigation system demonstrates how technology can be effectively applied to solve real-world agricultural challenges.